Principals' Decision-Making Strategies and Teachers' Job Satisfaction in Kwara State Schools, Nigeria - Olaifa, Adeseko Sunday; Odumosu, Faruq Ajobi; Alao, Monsurat Iyabo; Ibrahim, Hafiz Babajide; Sagaya, Abiodun Amudalatu (LJPI UI Bunga Bangsa Cirebon, 2025)
Objective: This study aimed to examine the relationship between principals' decision-making strategies and teachers' job satisfaction in secondary schools in Kwara State, Nigeria. Novelty: This study provides a unique perspective by analyzing multiple decision-making strategies, including open-door, closed-door, consultation, and collaboration, and their varying impacts on teachers' job satisfaction, which has not been extensively explored in the Nigerian secondary school context. Methods: This study used a descriptive survey design. It involved 7675 senior secondary school teachers from 407 public schools in Kwara State. A sample of 297 respondents was selected from 825 teachers using Krejcie and Morgan's table and simple random sampling from 35 schools. Data were collected through a self-designed questionnaire,